Physiology and pathophysiology of cyclooxygenase-2 and prostaglandin E2 in the kidney - Rikke Nørregaard; Tae-Hwan Kwon; Jørgen Frøkiær (The Korean Society of Nephrology, 2015)
The cyclooxygenase (COX) enzyme system is the major pathway catalyzing the conversion of arachidonic acid into prostaglandins (PGs). PGs are lipid mediators implicated in a variety of physiological and pathophysiological processes in the kidney, including renal hemodynamics, body water and sodium balance, and the inflammatory injury characteristic in multiple renal diseases. Since the beginning of 1990s, it has been confirmed that COX exists in 2 isoforms, referred to as COX-1 and COX-2. Even though the 2 enzymes are similar in size and structure, COX-1 and COX-2 are regulated by different systems and have different functional roles. This review summarizes the current data on renal expression of the 2 COX isoforms and highlights mainly the role of COX-2 and PGE2 in several physiological and pathophysiological processes in the kidney.